Computational intelligence concepts to implementations - Eberhart, Russell C. (Elsevier/Morgan Kaufmann Publishers, 2007)
Explores a number of key themes, including self-organization, complex adaptive systems, and emergent computation. This title details the metrics and analytical tools needed to assess the performance of computational intelligence tools. It concludes with a series of case studies that illustrate a range of successful applications.